Autopercepção do estado de saúde, qualidade de vida e consumode recursos de saúde em uma população de aposentados de Belo Horizonte. - Fausto Aloisio Pedrosa Pimenta (2006)
The rapid aging process of the Brasilian population is accompanied by a similar change in the composition of the countrys work force.As the process of demographic transition comes on, many countries facethe aging of their population who is expected to have an impact on public policies directed to improve the well-being of its. One of the main issues related with the aging population, which is expected is the relationship between health status and retirement. The objective of this study is to determine association between self-rated health, quality of life and health care utilization in retirees in Belo Horizonte Minas Gerais. The brasilian version of the SF-36 was used in 87 retirees. The analysis included the chi-square and odds ratios estimated by multiple logistic regression.This study indicates that retirees who practices physical exercises and had been working after retired presents a good self-rated health and a better quality of life. This fact may direct policies to improve the well-being in persons who retire early. Our results indicate the need for simultaneous, comprehensive actions in the health sector, pre-retired and social services to address the main determinants of self-ratedhealth and quality of life in order to promote well-being among the retirees.